Usage of nicotine and alcohol – influence on the substances dependence therapy - Kucharska-Mazur, Jolanta; Samochowiec, Jerzy (Przewodnik Lekarza/Guide for GPs, 2011)
Nicotine dependence is a significant problem of alcoholics. Interactions of alcohol and nicotine contribute to somatic damages and psychiatric disorders. The authors of present paper analyze conditions, methods and time of therapeutic intervention.